Prussian blue analogs as battery materials - Hurlbutt, K; Wheeler, S; Capone, I; Pasta, M (Cell Press, 2018)
Context & Scale: In this work, we offer our perspective on a class of compounds known as Prussian blue analogs, a group of versatile cyano-coordination polymers. Originally commercialized in the dye industry, they have more recently been used in diverse energy technologies including energy storage, electrocatalysis, and thermal power generation. We address their role as components of the next generation of batteries with improved cycle life and power capability. Through a review of achievements from early electrochemical experiments to crystallographic breakthroughs to development of state-of-the-art electrodes, we outline how control over the crystal structure allows these materials' electrochemistry to be tuned for diverse uses. Despite recent advances, there remain conspicuous and fundamental questions about the structure-electrochemistry relationship that we identify. We adumbrate investigations using density functional theory calculations, synchrotron X-ray techniques, electrochemical tests, and technoeconomic analyses to answer these questions.